2018
DOI: 10.2339/politeknik.404006
|View full text |Cite
|
Sign up to set email alerts
|

Some Physical and Mechanical Properties of Impregnated Chestnut Wood with Natural and Chemical Agent Exposed to Outdoor Conditions

Abstract: Bu makaleye şu şekilde atıfta bulunabilirsiniz(To cite to this article): Yaşar M. ve Altunok M., "Some physical and mechanical properties of impregnated chestnut wood with natural and chemical agent exposed to outdoor conditions", Politeknik Dergisi, 22(2): 399-406, (2019).Erişim linki (To link to this article): http://dergipark.gov.tr/politeknik/archive ABSTRACT Wood preservatives have been widely used to extend the service life of wood. The most objectionable environment for wood is outdoor conditions. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Tannins can be obtained from the bark of mimosa, acorn, chestnut, sumac, tara, and bark of various pine species. Tannins are used in many different fields such as leather manufacturing, adhesives, additives to beverages, and medical applications [14,25,26,37]. In this study, tannins were dissolve in distille water at 80 °C to a concentration of 10%.…”
Section: Materials and Methods 21 Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tannins can be obtained from the bark of mimosa, acorn, chestnut, sumac, tara, and bark of various pine species. Tannins are used in many different fields such as leather manufacturing, adhesives, additives to beverages, and medical applications [14,25,26,37]. In this study, tannins were dissolve in distille water at 80 °C to a concentration of 10%.…”
Section: Materials and Methods 21 Materialsmentioning
confidence: 99%
“…In another work, Yaşar and Altınok (2019) investigated effect of natural tannin solutions (pine, acorn) and and chemical impregnation (imersol aqua, timbercare aqua) on characteristic of woods. As a result, they reported that natural tannin solutions could be an alternative to chemical impregnation materials in wood samples exposed to outdoor conditions [26]. Tondi et al (2012) analyzed the changes in mechanical and fire properties of Scotch pine and European beech samples after impregnation with tannin-based chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The wood material which stays in natural conditions can get destroyed in under 5 years (except some certain wood species) (Ors and Keskin, 2001;Ozcifci, 2009;Tan and Peker, 2015a;Tan and Peker, 2015b;Keskin and Daglioglu, 2016). The service life of wood can increase with impregnation with wood preservative materials (Archer and Lebow, 2006;Hill, 2006;Tondi et al, 2012, Sandberg et al, 2017, Yasar and Altunok, 2019. Impregnation is the process of penetrating wood with substances with different contents with the purpose of preventing rotting, burning and dimensional work in wood material (Kurtoglu, 2000;Hill, 2006, Ayar, 2008Akgul and Apay, 2014a;Akgul and Apay, 2014b;Esteves et al, 2014.…”
Section: Introductionmentioning
confidence: 99%